Single- and Double-Lung Ventilation in Infants and Children Undergoing Thoracoscopic Lung Resection - Dingemann, Carmen; Zoeller, Christoph; Bataineh, Ziad; Osthaus, Alexander; Suempelmann, Robert; Ure, Benno (European Journal of Pediatric Surgery, 2013)
Introduction Video-assisted thoracoscopic surgery (VATS) has gained wide acceptance for the pediatric population. Single-lung ventilation (SLV) has been suggested for thoracoscopic lung resection to provide better surgical exposure, but its role and sequelae compared with double-lung ventilation (DLV) have not been determined. The aim of this study was to investigate the feasibility and effects of SLV and DLV in infants and children undergoing thoracoscopic lung resection.Patients and Methods Written informed consent from all guardians for anonymized data analysis and approval by the Institutional Review Board were obtained. A retrospective study on a consecutive series of infants and children who underwent thoracoscopic lung resection during an 11 years period was performed. SLV was selected mainly in lesions localized in the upper, middle, and/or central lung for reasons of surgical exposure. Patients with lower lobe lesions and those who underwent atypical resections were preferably operated under DLV. End points were conversion rate, duration of postoperative ventilation, and perioperative complications, such as, atelectasis or pneumonia.Results Of 114 pediatric patients (58 female and 56 male; ratio 1.04:1) with a mean age of 7.1 years (3 days to 18.1 years), 62 patients underwent DLV and 52 patients underwent SLV for thoracoscopic lung resection. There were no significant differences between the two groups for conversion rate (DLV 8.1 vs. SLV 6.1%; p = 0.53), prompt extubation (DLV 50 vs. SLV 34.6%; p = 0.14), and postoperative atelectasis (DLV 35.5 vs. SLV 25%; p = 0.32). No major cardiorespiratory events, such as bleeding or pneumonia, were observed. No perioperative mortality occurred.Conclusions This is the first study on safety, effectiveness, and outcome of SLV and DLV in pediatric patients undergoing thoracoscopic lung resection. Our data suggest that both SLV and DLV can be safely performed with similar low rate of surgical complications, when specific selection criteria are applied.
Keywords: single-lung ventilation; thoracoscopy; children; lung resection; pediatric surgery